Monetary financing in the euro area: A free lunch? - Silke Tober (Intereconomics, 2015)
Two recent proposals for overcoming the euro area crisis make the case for monetary financing of the public sector. Watt proposes that the ECB finances public investment directly, while Pâris and Wyplosz contend that public debt may be effectively restructured by burying parts of it in the balance sheet of the Eurosystem. Both proposals place the ECB at the centre of matters generally considered to be fiscal in order to circumvent existing fiscal and political constraints. This paper argues that both proposals fudge the line between monetary and fiscal policy, thereby ignoring valid reasons for separating these two macroeconomic policy areas.
Keywords: 330; Geldpolitik; Finanzpolitik; Öffentliche Investition; Bankrechnungslegung; Zentralbank; Eurozone